The analysis of the doctors' perspective on the traditional, complementary and alternative medicine - Marković-Petrović Gordana D.; Belamarić Gordana B. (Srpsko lekarsko drustvo, 2019)
Introduction: The application of traditional, complementary and alternative medicine (TCAM) has been increasing and gaining popularity over the past two decades. This is mostly the result of the patients changing their lifestyle and searching for new forms of non-invasive, natural therapy. Even though the World Health Organization has recognized the importance of TCAM, the majority of doctors are still not ready to accept TCAM as a legitimate form of medical treatment. Thus many patients use TCAM without doctors' consent, which can result in delaying or avoiding the use of adequate treatments in conventional medicine. Also, there is the possibility of interaction between conventional medications and the preparations used in TCAM. All of this can potentially result in a major public health problem. Aim: The aim of this research is to determine the doctor's perspective about TCAM, and to form a valid instrument that would be used in this and all future trials. Methods: A questionnaire was used as the data collection tool. The analyses used in the statistical processing of the obtained results are: the multiple correspondence analysis, discriminant analysis, Mann-Whitney testing and the ROC curve procedure. Results: 110 doctors were examined, 24 of whom have been trained in one of the TCAM methods. By multiple correspondence analysis, regarding the responses, three dimensions of TCAM acceptance have been identified. The total explained variance is 98.36%, and the average value of the Cronbach's Alpha coefficient for all three dimensions is 0.929. Conclusions: Educating physicians to use traditional, complementary and alternative medicine plays a decisive role in their acceptance of these methods. It is also of great importance, since there is an increasing number of patients who use TCAM methods without medical supervision.